GROWTH, REPRODUCTION, AND DEATH RATES OF ESCHERICHIA COLI AT INCREASED HYDROSTATIC PRESSURES - Zobell, Claude E. (1962)
ZoBell, Claude E. (University of California, La Jolla) and Andre B. Cobet. Growth, reproduction, and death rates of Escherichia coli at increased hydrostatic pressures. J. Bacteriol. 84:1228–1236. 1962.—Pressures ranging from 100 to 500 atm were found to retard the growth and reproduction of Escherichia coli in nutrient medium. Reproduction (as manifested by cell division or an increase in the number of viable cells) was retarded more than was growth (as manifested by increase in cell size or the formation of biomass). When incubated near the threshold of pressure tolerance (about 475 atm at 30 C), some cells of E. coli grew into long slender filaments showing little evidence of fission or cell division. Compression prolonged the lag phase of E. coli in nutrient medium, particularly at pressures higher than 400 atm. The inhibiting effects of pressure on reproduction and growth were found to be less at 30 than at 20 or 40 C. Pressures of 400 to 1,000 atm accelerated the death rate of E. coli cultures in nutrient medium. The lethal effects of pressure were greater at 40 than at 30 C and greater at 30 than at 20 C.